Cancer Care Delivery and Women’s Health: The Role of Patient Navigation - Krok-Schoen, Jessica L.; Oliveri, Jill M.; Paskett, Electra D. (Frontiers in Oncology, 2016)
Background: Patient navigation (PN) is a patient-centered health care service delivery model that assists individuals, particularly the medically underserved, in overcoming barriers (e.g., personal, logistical, system) to care across the cancer care continuum. In 2012, the American College of Surgeons Commission on Cancer (CoC) announced that healthcare facilities seeking CoC-accreditation must have PN processes in place starting January 1, 2015. The CoC mandate, in light of the recent findings from centers within the Patient Navigation Research Program, and the influx of PN interventions, warrants the present literature review. Methods: PubMed and Medline were searched for studies published from January 2010 to October 2015, particularly those recent articles within the past 2 years, addressing PN for breast and gynecological cancers, and written in English. Search terms included patient navigation, navigation, navigator, cancer screening, clinical trials, cancer patient, cancer survivor, breast cancer, gynecological cancer, ovarian cancer, uterine cancer, vaginal cancer, and vulvar cancer. Results: Consistent with prior reviews, PN was shown to be effective in helping women receive cancer screenings, receive more timely diagnostic resolution after a breast and cervical cancer screening abnormality, initiate treatment sooner, receive proper treatment, and improve quality of life after cancer diagnosis. However, several limitations were observed. The majority of PN interventions focused on cancer screening and diagnostic resolution for breast cancer. As observed in prior reviews, methodological rigor (e.g., randomized controlled trial design) was lacking. Conclusion: Future research opportunities include testing PN interventions in the post-treatment settings and among gynecological cancer patient populations, age-related barriers to effective PN, and collaborative efforts between community health workers and patient navigators as care goes across segments of the cancer control continuum. As PN programs continue to develop and become a standard of care, further research will be required to determine the effectiveness of cancer PN across the cancer care continuum, and in different patient populations.